2015
DOI: 10.3109/15419061.2016.1155565
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Aggravate Hypoxia-Induced Cardiac Microvascular Endothelial Cell Injury via Peroxynitrite: Protection by Tongxinluo

Abstract: Activated macrophages contribute to endothelial dysfunction; however, it is unclear how peroxynitrite contributes to macrophage-mediated human cardiac microvascular endothelial cell (HCMEC) injury in hypoxia. In macrophage-HCMEC co-cultures subjected to hypoxia, there was an increase in hypoxia-inducible factor (HIF)-1a, HIF-2a, inducible nitric oxide synthase (iNOS), endothelin-converting enzyme (ECE)-1 and cyclooxygenase-2 (COX-2), and concomitant decrease in prostacyclin synthase (PGIS). This was mimicked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…TXL is a multifunctional traditional Chinese medicine reported to exert pleiotropic effects such as anti-fibrosis (Chen W. et al, 2008 ; Bai et al, 2013 ; Wang X. et al, 2016 ), anti-inflammation (Wang et al, 2015 ), anti-atherogenesis (Wu et al, 2015 ), anti-apoptosis (Cui et al, 2014 ; Wei et al, 2016 ) and improved microvascular barrier function (Liu et al, 2013 ; Li et al, 2015 ; Qi et al, 2015 ; Zheng et al, 2015 ). This multitude of activities can be explained by the variety of active ingredients in TXL (Cheng et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…TXL is a multifunctional traditional Chinese medicine reported to exert pleiotropic effects such as anti-fibrosis (Chen W. et al, 2008 ; Bai et al, 2013 ; Wang X. et al, 2016 ), anti-inflammation (Wang et al, 2015 ), anti-atherogenesis (Wu et al, 2015 ), anti-apoptosis (Cui et al, 2014 ; Wei et al, 2016 ) and improved microvascular barrier function (Liu et al, 2013 ; Li et al, 2015 ; Qi et al, 2015 ; Zheng et al, 2015 ). This multitude of activities can be explained by the variety of active ingredients in TXL (Cheng et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…CMECs, a special cell type derived from coronary microvessels, play a major role in promoting angiogenesis and delivering oxygen to myocardium. The fact that HIF‐1α is elevated under hypoxic conditions has been confirmed in most types of endothelial cells, for example, human/rat cardiac microvascular endothelial cells and human umbilical vein endothelial cells (HUVECs) 28, 29, 30. As is known, activated HIF‐1α and its downstream effector VEGF are key regulators which can protect endothelial cells from hypoxia‐induced impairment and promote angiogenesis and cell migration 7.…”
Section: Discussionmentioning
confidence: 94%
“…The fact that HIF-1a is elevated under hypoxic conditions has been confirmed in most types of endothelial cells, for example, human/rat cardiac microvascular endothelial cells and human umbilical vein endothelial cells (HUVECs). [28][29][30] As is known, activated HIF-1a and its downstream effector VEGF are key regulators which can protect endothelial cells from hypoxia-induced impairment and promote angiogenesis and cell migration. 7 In the present study, however, with long-time hypoxia, the protective mechanism initiated by adaptive HIF-1a elevation seems decompensated and not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular injury after chronic hypoxia usually leads to endothelial injury and structural damage to tight junctions, TXL could promote endothelial cell proliferation and reverse the expression of tight junctions' proteins in vivo and in vitro (Zheng et al, 2015 ). Additionally, we found that TXL could regulate gene expression in hypoxia-treated human cardiac microvascular endothelial cells (CMECs) (Li Y. N. et al, 2015 ) and attenuate human CMEC injury via inhibiting peroxynitrite, which contributed to macrophage-mediated human CMEC injury (Wang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%